Conjugate heat transfer characteristics of effusion cooling under realistic swirl flow in a three-sector gas turbine model combustor. (August 2022) - Ji, Yongbin; Ge, Bing; Zang, Shusheng
Highlights: Convective heat transfer inside effusion holes contributes greatly to the heat removal even the film layer is damaged. The full-coverage cooling film is developed and reachable after swirl flow-cooling jets intense interaction. The swirl flow impinging location is not influenced by amount of main and cooling flows. · Increment of coolant. Abstract: Conjugate heat transfer characteristics of the effusion cooling applied on the swirl-stabilized combustor liner is experimentally and numerically investigated in a three-nozzle gas turbine model combustor at non-reacting flow conditions. The interaction between the strong swirl main flow and multi-hole cooling jets inclined at 30° is stressed by varying the pressure drop across the nozzle ( Δ P m  = 3–5%) and effusion plate ( Δ P e  = 0–2%). The expanding swirl flow impinges on the liner wall and thus inhibits the injection of coolant via effusion holes locally, causing non-uniform cooling protection along both streamwise and lateral directions. The overall cooling effectiveness in the impingement region is much lower than other regions on the cooled plate. Despite of the detrimental effect of the main flow impingement on the formation of the effusion film, the cooling function doesn't totally collapse due to the great capability of heat removal through convection heat transfer inside the cooling holes. Superposition effect induced full coverage of film on the wall is distinguished at further downstream. Enhancing the cooling air amount weakens the consequence of the mainstream impingement and lead the full coverage initial location to move upwards.